THE INVOLVEMENT OF TELAGA BATIK UMKM IN PROMOTIONAL COMMUNICATION IN BEKASI REGENCY - Eltian Asfahami, Arisza; Imaddudin (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
The tourism industry has significant potential to drive economic and social advancement, with UMKM Telaga Batik in Cikarang Barat, Bekasi Regency, serving as an active example of supporting this sector through its unique regional Batik products. This study aims to understand the involvement of UMKM Telaga Batik in promotional communication in Bekasi Regency, using a descriptive qualitative method through observation, interviews, and documentation. The results show that Telaga Batik has successfully shifted its promotion strategy from traditional media such as television and radio to digital media, especially through social media platforms like Instagram. Collaboration with television stations and government support through offline and online promotions has also increased the visibility of Telaga Batik to the public. Active involvement in the local community and government support are key factors in strengthening consumer loyalty and the positive image of Telaga Batik. Effective promotional strategies, such as discounts, social media usage, and participation in UMKM exhibitions, have proven effective in raising public awareness of Telaga Batik products. Telaga Batik not only produces local products but also serves as a promotional agent and bearer of Bekasi Regency's cultural identity. Additionally, good relationships with local communities such as Paguyuban Abang Mpok Bekasi Regency help strengthen the relationship between UMKM and the local community, which in turn supports business success.